PENGARUH PERASAN LIDAH BUAYA (Aloe vera) TERHADAP PERTUMBUHAN Staphylococcus aureus - Azizah, Fitrotin (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PENGARUH PERASAN LIDAH BUAYA (Aloe vera) TERHADAP PERTUMBUHAN  Staphylococcus aureusFitrotin Azizah, SSTAkademi Analis Kesehatan UNMUH Surabaya Abstract                                                                                     Lidah buaya (Aloe vera) is one efficacious medicinal plants to cure various diseases. Extract Lidah Buaya (Aloe vera) has various activities such as antibacterial against Staphylococcus aureus, Klebsiella pneumoniae, Mycobacterium tuberculosis. Staphylococcus aureus can cause an infection, it is necessary to research on antibacterial effect of aloe vera on the growth of Staphylococcus aureus. This type of research is experimental in order to determine the concentration of the smallest on Aloe vera juice can inhibit the growth of Staphylococcus aureus bacteria. The study design used is the Experimental Design posttest only. Based on the study, the concentration of aloe vera juice 100%, 90%, 80%, 70%, 60%, 50%, and 40% can inhibit the growth of Staphylococcus aureus. While the concentration of Aloe vera juice 30%, 20%, 10%, and 0% growth of Staphylococcus aureus occurs. The results Aloe vera juice 40%, 50%, 60%, 70%, 80%, 90%, and 100% showed no growth of Staphylococcus aureus occurs. Whereas at a concentration of 0%, 10%, 20% and 30% showed growth of germs. There is the influence of the concentration of aloe vera juice (Aloe vera) on the growth of Staphylococcus aureus.Keyword : Aloe vera, Staphylococcus aureus